Informatização da operação e da gestão de uma unidade de saúde de alta complexidade do sistema único de saúde (SUS): estudo de caso do instituto de medicina integral Prof. Fernando Figueira (Imip) sob o enfoque do isomorfismo institucional - Moraes, Marcio Fabio Paula de (2010)
This study seeks to identify and evaluate a choice made by Imip in the light of neo-institutional theory, using isomorphic mechanisms that are characteristic of the field of health organizations. It is a case study, whose main object of analysis is Imip, with a special emphasis on two models for computerizing operations and management, with a view to establishing which is the more appropriate for the specific features of the institution, including financial aspects and cost-benefit analysis. The first model is an in-house computer system; the second a ready-made management system sold by a company specializing in this technology. The methodology includes bibliographical documentary and field research. The study is guided theoretically by neo-institutional theory and the field work involved simple observation, with a view to comparing variables from the two models under evaluation, and data collection using two questionnaires: one open questionnaire to be applied to IMIP managers and one mixed questionnaire to be applied to one hundred randomly-selected collaborators and system-users. The findings included clear references to isomorphism, chiefly of the mimetic kind, in the perceptions of respondents. On completion of the research, it was possible to conclude that contracting a hospital management system already available on the market, which has been designed and is sold by a technology company specializing in the health sector, is the best option for the organization, since the similarities that exist between the processes of this Institute and those contained in the system are much more significant than any specific feature of the Institute. Another relevant factor concerned the high cost involved in a single institution developing and maintaining singlehanded an up-to-date system that is in compliance with the normative and technical requirements of health organizations and the information quality standards stipulated by the Brazilian National Health System.